How the stock markets work - Chapman, Colin (London, 2011)
How the Stock Markets Work has long been an established favourite for anyone who needs a straightforward, accessible introduction to the stock markets. This guide concisely explains how the stock markets have developed as well as how they operate today and is a must-buy for anyone looking to learn more about this sector of the financial industry.
Keywords: Stock markets